2015
DOI: 10.1016/j.compag.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Proximal hyperspectral sensing and data analysis approaches for field-based plant phenomics

Abstract: a b s t r a c tField-based plant phenomics requires robust crop sensing platforms and data analysis tools to successfully identify cultivars that exhibit phenotypes with high agronomic and economic importance. Such efforts will lead to genetic improvements that maintain high crop yield with concomitant tolerance to environmental stresses. The objectives of this study were to investigate proximal hyperspectral sensing with a field spectroradiometer and to compare data analysis approaches for estimating four cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 43 publications
1
50
0
1
Order By: Relevance
“…Similar results were obtained by Thorp et al (2015), studying cotton cultivars. These authors found higher variability of reflectance in the near infrared (760-1350 nm) compared with the visible (400-700 nm) and medium infrared (1450-2400 nm).…”
Section: Resultssupporting
confidence: 76%
“…Similar results were obtained by Thorp et al (2015), studying cotton cultivars. These authors found higher variability of reflectance in the near infrared (760-1350 nm) compared with the visible (400-700 nm) and medium infrared (1450-2400 nm).…”
Section: Resultssupporting
confidence: 76%
“…/j.fcr.2017 green fraction, leaf area index (LAI), and the leaf biochemistry, e.g., chlorophyll and nitrogen contents (Comar et al, 2012;Jay et al, 2015;Thorp et al, 2015). An accurate retrieval of such structural and biochemical parameters is critical for plant phenotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors show that, in comparison to univariate approaches, multivariate approaches were able to provide better results in detection of early stages of biotic stress (Römer et al 2011), or in the predict nitrogen and water content (Kusnierek and Korsaeth 2015). Another approach, based on radiative transfer models, seems promising for field phenotyping, as this takes into account biochemical and structural properties of the leaf and canopy (Thorp et al 2015).…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…By using the BRDF output, the effects of canopy structure, composition and geometry, as well as illumination on the spectra collected, can be corrected for. Moreover, model inversion techniques and reflectance measurements can be used to obtain input parameters of the PROSAIL model, such as chlorophyll concentration, dry matter content or leaf water thickness (Thorp et al 2015). A challenging approach to overcoming issues caused by canopy geometry may be through the fusion of 3D point cloud images with 2D spectral images, whereby each point cloud within a 3D image is assigned a value corresponding to the same point in an image from a spectral image, however this is an avenue requiring further exploration.…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%